Effects Of Neuroscience-Based Thinking (NBT) And Thinking Skills (TS) Strategies On Thinking And Emotion Among Primary Schools Pupils - Alghafri, Ali Salim Rashid (2011)
The aim of this study is to investigate the effects of Neuroscience-Based Thinking (NBT) strategy and Thinking Skills (TS) strategy on creative thinking and the performance of science tasks (thinking and emotion) among Malaysian pupils in primary schools. This study used quasi-experimental research design with one control group and two experimental groups. Ninety eight pupils enrolled in standard five during the 2010 educational year formed the sample. The two experimental groups were named NBT and TS while prevalent strategy (P) as the control group. The instruction was carried out by three different science teachers. These three groups were measured twice (pretest and posttest) of three different instruments: the Test of Creative Thinking (TCT), Science Task of Thinking (STT) and of Emotion (STE). The instruments' reliabilities are good as showed by Cronbach alpha and Pearson correlation. Inferential statistics, namely two ways ANCOVA and MANCOVA tests, and LSD post hoc method were used at α .05 level to determine statistically significant differences between study groups. The results showed that there were significant differences between groups. The result of the test of creative thinking in science and its sub-skills (fluency, flexibility and originality) indicated that the pupils in NBT group scored higher as compared to TS and P groups in all but one sub-skill (fluency) where TS group has better score. Likewise, the TS pupils are higher than P pupils except in originality where both were similar. Similarly, the results of thinking and emotion of science tasks revealed that the pupils of NBT scored higher than TS and P groups in their thinking and emotion. Furthermore, the results revealed that there were no significant differences in posttest between gender in all groups. Similarly, there were no significant in interaction effects in post-test between all groups and both gender on all variables yet the female pupils of TS group have high scores in fluency. Therefore, the study recommends that educators should work to enhance learning and creativity among pupils by employing neuroscience principles in teaching and learning process by integrating them into curriculum.